Comparative Analysis of Rote Learning on High and Low Achievers in Graduate and Undergraduate Programs - Ambreen Ahmed; Nawaz Ahmad (Journal of Education and Educational Development, 2020)
A survey was conducted to study the preferred learning strategies; that is, surface learning or deep learning of undergraduate and graduate male and female students and the impact of the preferred strategy on their academic performance. Both learning strategies help university students to get good scores in their examinations to meet the demands of industry in workforce. Quantitative research method was used to determine the impact of learning strategy on academic achievements. The R-SPQ2F questionnaire was sent to 103 students through Google forms and hard copies through snowball sampling technique. The results show that rote learning and academic performance are inversely related to each other. In high achievers, deep learning is significant as compared to low achievers. Furthermore, comparative analysis of learning styleson males and females showed that both preferred deep learning strategy equally. Learning strategy is not related to education level of students because there is no difference among preferred learning strategies of graduate and undergraduate students.
Keywords: academic performance, deep learning, rote learning, surface learning